PENGARUH SIMULASI TRIASE START TERHADAP KETERAMPILAN TRIASE DALAM MENGHADAPI BENCANA GEMPA BUMI PADA KARANG TARUNA ROGOITAN, BANTUL: THE EFFECT OF START TRIAGE SIMULATION ON TRIAGE SKILLS IN FACING THE EARTHQUAKE DISASTER IN KARANG TARUNA ROGOITAN, BANTUL - Ahmad Rivaldi Ismail A. Utina; Ririn Zuhairini; Heri Puspito (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Earthquakes are a serious threat in Indonesia that threaten lives, causing fatalities. The 2006 Bantul earthquake measuring 5.9 on the Richter scale rocked the Yogyakarta and Central Java regions with 19,202 fatalities. In emergency situations, triage knowledge and skills are very important, but the Padukuhan Rogoitan area has never received disaster triage training or simulation. The aim of this research aims to determine the effect of triage simulation on triage skills in dealing with disasters in youth organizations. The method used is a simulation method of carrying out independent triage by youth organizations involving 30 members of the Padukuhan Rogoitan Youth Organization, Pendowoharajo District. Using the Wilcoxon test. The results show that before the simulation, 73.3% of respondents were in the "Quite Skilled" category, while after the simulation, 86.7% of respondents managed to reach the "Very Skilled" category. The Wilcoxon test shows a significance value of 0.000. Triage simulation needs to be integrated into the youth organization's routine training program.